2020
DOI: 10.1158/2326-6066.cir-20-0034
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody Targeting ICOS Increases Intratumoral Cytotoxic to Regulatory T-cell Ratio and Induces Tumor Regression

Abstract: An antibody targeting ICOS increases intratumoral cytotoxic to regulatory T cell ratio and induces tumor regression Anti-tumour activity triggered by an anti-ICOS antibody

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Several studies have shown that the stimulation of these receptors reduces the immunosuppressive function of Tregs, leading to the activation of effector T cells. 132 133 Antibodies that act as agonists of OX40, such as MEDI6469 134 (NCT02274155), GITR, such as MK-4166 135 (NCT02132754), and ICOS, such as KY1044 136 (NCT03829501), are currently being investigated.…”
Section: Targeting Chemokine Receptors and Immune Checkpoint Molecules On Tregsmentioning
confidence: 99%
“…Several studies have shown that the stimulation of these receptors reduces the immunosuppressive function of Tregs, leading to the activation of effector T cells. 132 133 Antibodies that act as agonists of OX40, such as MEDI6469 134 (NCT02274155), GITR, such as MK-4166 135 (NCT02132754), and ICOS, such as KY1044 136 (NCT03829501), are currently being investigated.…”
Section: Targeting Chemokine Receptors and Immune Checkpoint Molecules On Tregsmentioning
confidence: 99%
“…KY1044, a fully human IgG1 antibody bounding to ICOS, induced sustained depletion of ICOS + Treg cells and increased the intra-tumoral Teff/Treg ratio. This KY1044 monotherapy has been demonstrated to improve the anti-PD-L1 efficacy in cancers [ 373 ]. Tregs-targeted therapy combined with ICIs can attenuate Treg-mediated drug resistance and increase tumor cell sensitivity to treatment, thereby promoting tumor regression.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Teffs, Tregs generally express a higher level of ICOS. In preclinical models, the differential expression of ICOS on Tregs and Teffs was exploited, and the anti-ICOS agonistic antibody was demonstrated to induce sustained depletion of ICOShigh Tregs and activate ICOS-low Teffs, resulting in an increase in Teffs/Tregs ratio in the TME, further enhancing the antitumor efficacy of the ICIs [17]. At least 6 ICOS antibodies have been tested in clinical trials: JTX-2011, GSK-3359609, MEDI-570, BMS-986225, XmAb23104, and KY1044 [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed, paraffin-embedded tissue sections (5-µm thickness) of each patient were retrieved from the archived tissues of the Department of Pathology, NTUH. A modified, sequential multiplex IHC assay was performed to evaluate ICOS and Foxp3 expression by procedures as described previously [17]. Briefly, tissue slides were deparaffinized, rehydrated, and autoclaved in citrate buffer (pH 6.0) for 10 min using a decloaking chamber for antigen retrieval, followed by blocking with hydrogen peroxide and then Background Sniper (BioCare Medical) to reduce nonspecific background staining.…”
Section: Ihc Stainingmentioning
confidence: 99%
See 1 more Smart Citation